Study of BaTiO₃ ceramics doped with Mn and Ce or Nb and Sr - Slipenyuk, A.M.; Glinchuk, M.D.; Bykov, I.P.; Yurchenko, L.P.; Mikheev, V.A.; Frenkel, O.A.; Tkachenko, V.D.; Garmash, E.P. (Condensed Matter Physics, 2003)
ESR study of BaTiO₃ ferroelectrics doped with cerium or with niobium and
strontium, both types of samples being doped with manganese, was performed
at room temperature. In the samples of the first type the most intensive
line with g-factor 1.9612 was shown to originate from paramagnetic
center Ti³⁺–Ce³⁺. The small intensity line was related to Fe³⁺–Vo center,
which can be unavoidable impurity in BaTiO₃.
In the samples doped with strontium, the six lines intensive spectrum,
which corresponds to hyperfine structure of Mn²⁺, was observed. The intensity
of the spectrum was shown to decrease with strontium concentration
increase. This effect was supposed to be related to the decrease of the
grain sizes that results in migration of manganese and, possibly, niobium
ions. The influence of these impurities, of their charge states and positions
in crystalline lattice of BaTiO₃ on the PTCR effect is discussed. Представлено результати ЕПР досліджень сегнетоелектричної кераміки BaTiO₃ двох серій: легованої церієм та марганцем або ніобієм, стронцієм та марганцем, при кімнатній температурі. Показано,
що у зразках першої серії найбільш інтенсивна лінія з g-фактором
1.9612 належить до парамагнітного центру Ti³⁺–Ce³⁺. Лінії малої інтенсивності належать до центру Fe³⁺–Vo (пов’язаного з неконтрольованою домішкою заліза у зразках) та до іону Mn²⁺.
В другій серії зразків спостерігався спектр, який відповідає надтонкій структурі іону Mn²⁺. Інтенсивність цього спектру зменшувалась
із збільшенням концентрації стронцію. Можливо цей ефект пов’язаний із зменшенням розмірів зерен та міграцією марганцю та, можливо ніобію, у міжзерновий простір. Обговорюється вплив домішок,
їх зарядового стану та позиції у кристалічній ґратці на ефект позитивного температурного коефіцієнту опору.